Neutralizing antibody levels detected early after mRNA-based vaccination do not predict by themselves subsequent breakthrough infections of SARS-CoV-2 - Alonso, Roberto; Gil-Manso, Sergio; Catalán, Pilar; Sánchez-Arcilla, Ignacio; Marzola, Marco; Correa-Rocha, Rafael; Muñoz, Patricia; Pion, Marjorie; , the Gregorio Marañón Microbiology-ID COVID-19 Study Group (Frontiers in Immunology, 2024)
The development of mRNA vaccines represented a significant achievement in response to the global health crisis during the SARS-CoV-2 pandemic. Evaluating vaccine efficacy entails identifying different anti-SARS-CoV-2 antibodies, such as total antibodies against the Receptor Binding Domain (RBD) of the S-protein, or neutralizing antibodies (NAbs). This study utilized an innovative PETIA- based kit to measure NAb, and the investigation aimed to assess whether levels of anti-RBD IgG and NAb uniformly measured 30 days after vaccination could predict individuals at a higher risk of subsequent infection in the months following vaccination. Among a cohort of healthy vaccinated healthcare workers larger than 6,000, 12 mRNA-1273-and 115 BNT162b2-vaccinated individuals contracted infections after the first two doses. The main finding is that neither anti-RBD IgG nor NAb levels measured at day 30 post-vaccination can be used as predictors of breakthrough infections (BI). Therefore, the levels of anti-SARS-CoV-2 antibodies detected shortly after vaccination are not the pivotal factors involved in antiviral protection, and other characteristics must be considered in understanding protection against infection. Furthermore, the levels of anti-RBD and NAbs followed a very similar pattern, with a correlation coefficient of r = 0.96. This robust correlation would justify ceasing the quantification of NAbs, as the information provided by both determinations is highly similar. This optimization would help allocate resources more efficiently and speed up the determination of individuals' humoral immunity status.